Widespread recognition of 5' splice sites by noncanonical base-pairing to U1 snRNA involving bulged nucleotides - Bennett, C. Frank (2013)
An established paradigm in pre-mRNA splicing is the recognition of the 5′ splice site (5′ss) by canonical base-pairing to the 5′ end of U1 small nuclear RNA (snRNA). We recently reported that a small subset of 5′ss base-pair to U1 in an alternate register that is shifted by 1 nucleotide. Using genetic suppression experiments in human cells, we now demonstrate that many other 5′ss are recognized via noncanonical base-pairing registers involving bulged nucleotides on either the 5′ss or U1 RNA strand, which we term “bulge registers.” By combining experimental evidence with transcriptome-wide free-energy calculations of 5′ss/U1 base-pairing, we estimate that 10,248 5′ss (∼5% of human 5′ss) in 6577 genes use bulge registers. Several of these 5′ss occur in genes with mutations causing genetic diseases and are often associated with alternative splicing. These results call for a redefinition of an essential element for gene expression that incorporates these registers, with important implications for the molecular classification of splicing mutations and for alternative splicing.